The Correlation between Patients' Perception of Food Taste and Menu Variation with The Covid-19 Patients' Food Acceptance: HUBUNGAN PERSEPSI PASIEN TERHADAP RASA MAKANAN DAN VARIASI MENU DENGAN DAYA TERIMA PASIEN COVID-19 - Chyntia Apris Christiwan; Siti Rahayu Nadhiroh; Widati Fatmaningrum; Nono Tri Nugroho; Thinni Nurul Rochmah (Media Gizi Indonesia, 2022)
Food acceptance is patient's ability to spend food served, while in this study measured using food waste. In Covid-19 patients,  it is necessary to pay attention of their food intake in order to optimize body's immune system. Improved immune system could help faster healing process. Thus, observing factors that affects food waste such as patients’ perception and menu variation are needed.  This study was conducted to analyze correlation between patient perceptions of food taste and menu variations with food waste in patients at the Covid-19 Indrapura Field Hospital. This study used a cross-sectional design. Sample was selected using the accidental sampling technique, 148 respondents were selected. Data was analyzed by using Pearson correlation test. Most of respondents were male (60.8%), aged 15-39 years (63.5%), and had a length of stay of 7 days (58.1%). Most of the respondents admitted that food taste was good and very good (90.5%), as well as menu variations were classified as good and very good (89.2%), with average food waste of respondents was 10.4%. Statistical test show that there was a correlation between food taste (p value = 0.000) and menu variations (p value = 0.005) with food waste Covid-19 patients. It is concluded that there is a significant correlation between food taste and menu variations with the food waste among Covid-19 patients. Though it meets hospital food waste standards, it is still important to pay attention to the things related to food taste and menu variations to keep the food waste below minimum standards.